(untitled) (TAJ: Journal of Teachers Association, 2018)
This cross-sectional type of descriptive study was undertaken to assess the awareness and practice of hand-washing among children in three villages of Puthia Upazila, Rajshahi District, Bangladesh. A total of 1152 children aged 5 – 18 years old were purposively selected from the study area. Majority (96%) of them was students of primary or secondary grade. A few were involved in business, farming, service and others. Face to face interview was conducted with the help of a semi structured questionnaire on the variables of interest. Nearly half (49.5%) of the respondents was 11-15 years and the rest >15 years old. Male-female distribution was almost equal. Fathers of the children were service-holder (18.7%), businessman (28.6%), farmer (26.1%) and day-laborer/rickshaw puller (26.5%). Nearly 60% of respondents belonged to poor family having monthly income Taka < 10000. Majority (97.1%) of the respondents was aware of the importance of hand washing and 75% perceived that diseases could be prevented through hand washing. More than 90% of the respondents were used to using soap and water for washing hands and over 80% washed hands regularly. Over three-quarters (77.8%) were accustomed to washing hands in school before tiffin. Most (81.8%) of the respondents used sanitary latrine for defecation. The use of soap-water for washing hands after defecation was significantly higher in older children (> 12 years) than that in younger children (≤ 12 years) (p = 0.020). The use of soap water for washing hands after defecation tends to be associated with children’s grade of education with higher tendency being observed in children of secondary and higher secondary school (p < 0.001). Children belonging to higher family income were more cautious in using soap/antiseptics (p < 0.001). The study concluded that perception and practice of hand-washing is appreciably high among rural children. However, older children, children studying in secondary grade and belonged to families with higher monthly income were more cautious about hand-washing. TAJ 2013; 26: 82-91